Effects of home confinement on intensity of physical activity during the COVID-19 outbreak in team handball according to gender, competition level and playing position: a worldwide study - Hermassi, S.; Bouhafs, E. G.; Bragazzi, N. L.; Ichimura, S.; Alsharji, K. E.; Hayes, L. D.; Schwesig, R. (Frontiers in Psychology, 2021)
Because of the COVID-19 pandemic, several restrictions have been implemented due to public health recommendations and subsequent government directives. Restrictions primarily include social distancing and home confinement which have serious implications for competitive athletes, and this research area is understandably scarce. As such, the aim of this investigation was to examine the effects of home confinement on intensity of physical activity (PA) during the COVID 19 outbreak in Team Handball. A total of 1359 handball players volunteered for the present investigation (age: 22.8 ± 6.0 years; body mass: 78.1 ± 14.9 kg; height: 1.76 ± 0.10 m; BMI: 25.0 ± 3.82 kg/m²). Participants answered an online version of the International Physical Activity Questionnaire (IPAQ) through Google Forms. Five research organizations administered the survey in Europe, Western Asia and the North Africa in several languages. Participants were asked to consider "before" and "during" confinement and conditions. The COVID-19 home confinement had a negative effect on PA intensity (vigorous, moderate, walking and overall). The largest changes across all parameters were detected for the sum parameter "all physical activity". METminutes/week (np 2=0.903) and minutes/week were significantly decreased (np 2 =0.861) compared before and during confinement. Additionally, daily sitting time significantly (p<0.001, np 2 =0.669) increased from 2.7 to 5.0 h per weekday. For gender, level of handball league, and playing position, no significant differences (group and interaction effects) were observed. However, for all parameters, significant time effects were observed. The largest change (in terms of np 2 ) in PA behavior for was found for walking (minutes per day: np 2 =0.755), with males displaying the greatest decrease (from 62.1 ± 10.6 to 29.9 ± 13.5 minutes per weekday; d=2.67). In terms of magnitude, the difference between genders regarding sitting was the greatest (difference in d=1.20). In conclusion, whilst COVID-19 measures are essential to preserve public health, PA was 3 compromised as a result of these interventions. COVID-19 confinement led to a large decrease in PA regardless of activity level, gender, and handball competition level, worldwide.